The Effect of Scaphoid Fracture Site on Scaphoid Instability Patterns - Werner, Frederick W.; St-Amand, Hugo; Moritomo, Hisao; Sutton, Levi G.; Short, Walter H. (Journal of Wrist Surgery, 2016)
Background Scaphoid fractures are common carpal fractures that are often misdiagnosed as wrist sprains and may go on to nonunion. The location of the fracture site may influence the stability of scaphoid nonunions.Purpose To determine whether the stability of a scaphoid nonunion depends upon the fracture's location, we tested the hypothesis that a simulated fracture distal to the apex of the scaphoid dorsal ridge will have greater interfragmentary motion than proximal.Methods Eleven cadaver wrists were moved through three wrist motions using a wrist simulator. In six wrists, a fracture was created distal to the scaphoid apex, and in five a fracture was created proximal to the apex. Sensors attached to the distal and proximal parts of each scaphoid measured the interfragmentary motion during wrist motion.Results In those wrists in which the scaphoid was sectioned distal to the apex, the distal fragment became significantly more unstable relative to the proximal fragment. It flexed, ulnarly deviated, and pronated. These motion changes were less when the scaphoid was sectioned proximally.Discussion Scaphoid fractures distal to the scaphoid apex will have greater interfragmentary motion. The mobility of the fragments at the fracture site is possibly a more important contributory factor of nonunion in scaphoid waist fractures than for proximal scaphoid fractures.Clinical Relevance Understanding the effect that the location of a scaphoid fracture has on the potential for nonunion may influence the modalities of treatment and follow-up.
Keywords: scaphoid fractures; scaphoid instability; carpal fractures